A ontological personalist approach to the dilemmas arising from the COVID-19 pandemic. - Moya, Graciela (2020)
The COVID-19 pandemic has dramatically exposed the lack of investment and management in the health system and the structural weaknesses of the social protection. The analysis of the dilemmas that arise as a sequence of decision-making to deal with the effects of the pandemic can leave aside the protection and promotion of the well-being of the person as the center of the organization of society, and focus only on the collective and institutional well-being. Ontological personalism as a bioethical theory allows a deep analysis of these dilemmas, since its philosophical base is centralized in the defense and promotion of the person, and in the search for the common good. This article analyzes the foundations of this bioethical current and the responses it can provide to the moral dilemmas exposed untimely by the COVID-19 pandemic.